Effect of Number of Beaters on the Performance of Household Hammer Mill - Oluwole, F. A.; Gujja, A.; Abubakar, A. K. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
A hammer mill with three different hammers having 2, 4 and 6 beaters was developed and evaluated. Maize and guinea corn were crushed at 3 different angular speeds of the hammer rotations (2600 rpm, 3000 rpm and 3400 rpm). Each beater was fixed on the shaft at a time and machine was started. As soon as the machine reached the required speed, 500g of sample was fed into the crushing chamber through the feed hopper. The final product was collected, weighed. Fuel consumed during the operation and the time taken were recorded. The process was replicated 3 times for both maize and guinea corn using the 3 hammers. The result obtained during the evaluation revealed that the average milling efficiency and specific fuel consumption (sfc) for 6 beaters, 4 beaters and 2 beaters were 83.5 % and 3.8 l/h, 72.47 % and 2.07 l/h and 60.19 % and 0.94 l/h respectively. The average milling efficiency and sfc for maize and guinea corn were 72.18 % and 2.45 l/h and 71.93 %, 2.09 l/h respectively. Number of beaters and angular speed of beaters and their interactions significantly affected the milling efficiency at 5 % level. Number of beaters, angular speed of beaters, sample type and their interactions significantly affected the sfc at 5 % level.